(Invited) Monolithic Ge Integration on the 3 µm SOI Platform for 40 GHz Photodiodes. (8th September 2020) - Aalto, Timo; Vehmas, Tapani; Kapulainen, Markku; Heimala, Päivi; Delrosso, Giovanni; Sun, Fei; Gao, Feng
Abstract : Ge photodiodes were integrated on the 3 µm SOI platform, where the 3 µm thick Si waveguides offer ultra-low propagation losses (~0.1 dB/cm), ultra-dense integration (μm-scale bends), small polarization dependency (down-to-zero birefringence) and the ability to tolerate relatively high optical powers (>1W). A horizontal Ge PIN photodiode was monolithically integrated on the 3 µm SOI platform. It reached a 3 dB cutoff frequency of 40 GHz and 1.0 A/W responsivity at -1 V bias and 1.55 µm wavelength. Germanium was selectively grown into cavities in the 3 µm SOI layer and the Ge waveguide detector was patterned with the same hard mask with the Si waveguides to achieve waveguide self-alignment. The development of 40 GHz PDs was an important step in improving the feasibility of the 3 µm SOI platform in high-bandwidth applications.